ANALISIS BUSINESS MODEL CANVAS (BMC) PADA USAHA PUPUK HIJAU BERKELANJUTAN DI UNIVERSITAS TEUKU UMAR - Anwar, Saiful; Nugroho, Yoga (Universitas Galuh, 2023)
Organic fertilizer is a fertilizer that is often used by farmers. The need for organic fertilizer is experiencing rapid growth, because of the potential use of this organic fertilizer to maintain soil fertility and can improve plant quality. The Sustainable Green Fertilizer Business Group requires evaluation to generate new strategies to increase revenue and profits for the Sustainable Green Fertilizer Business Group. Slow business development affects the Sustainable Green Fertilizer business group. Every research is expected to be useful for all parties who read it and who are directly related to it. The benefits of this research are useful as one to analyze business strategies, namely using the Business Model Canvas (BMC) which can be used as a business tool in developing new and better strategies in the Sustainable Green Fertilizer business. The method used in this research is to use a descriptive analysis method, which answers the problems faced by the Sustainable Green Fertilizer business group in the form of case studies so that a broad picture is obtained during this research. From the results of this study, the Business Model Canvas (BMC) can help understand and explain what activities are carried out by the Sustainable Green Fertilizer business group so that it can generate profits for the Sustainable Green Fertilizer business group